Synchronous primary aneurysmal bone cysts: A rare case report and literature review - Noori Al Kadhim, DO; Akinyemi A Akintayo, MD; Alexander Ree, MD; Pedram Rezai, MD (Radiology Case Reports)
Aneurysmal bone cysts (ABCs) are rare benign osteolytic tumors which occur most frequently within the first two decades of life and can lead to pathological fractures. They have characteristic imaging and histologic features and have historically been classified into two types: primary ABCs, which are true neoplasms linked to specific oncogenes, and secondary ABCs, which are preceded by other bone lesions. The occurrence of multiple concurrent primary ABCs is exceedingly rare; with only a few cases reported in the published literature. Here, we present an unusual case of this condition, along with a review of the typical presentation, imaging and pathological findings, and available treatment options.